Precificação de ações da Bovespa pelo modelo de valor presente (MVP) - Mattos, João Vitor de (2015)
The fundamentals that make up the price of financial assets are of utmost importance to the economic agents. Among the existing finance theories have the Model of Present Value (MVP) which considers the current prices of securities as the sum of future dividends to be generated brought to their respective present value using a discount rate equivalent to required rate of return. The objective of this work is the application of MVP in the Brazilian market, testing the predictability of returns in a context of rational expectations will be a long-term relationship analysis of validation test between prices and dividends analyzing its stationary and cointegration relationship. For this two situations are considered in sequence in the first assume that the expected return will always be constant and then evaluate the model by assuming the return varies over time. The results obtained demonstrate that the pricing of financial assets in the Brazilian market is in line with the theory presented in the present value model there so a long-term relationship between prices and dividends.